2007
DOI: 10.1002/asia.200700211
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Solvent‐Trapped Products Obtained by Photolysis of Aryl Azides in 2,2,2‐Trifluoroethanol

Abstract: A series of nonfluorinated and fluorinated aryl azides with varied functionality patterns were irradiated in 2,2,2-trifluoroethanol with either a high-pressure or a low-pressure mercury lamp. Interestingly, one of the major products in these reactions was the result of the recombination of anilino and alkyl radicals to form the corresponding hemiaminal compounds. The structure of the recombination products was assigned unambiguously after proton/deuterium exchange experiments followed by MS and MS/MS analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…41) Isobe's LC-MS and MS/MS analysis combined with counting the exchangeable protons was a powerful technique to identify the trace amounts of natural products using deuterium oxide as an eluent. [42][43][44][45][46][47] Although the structure of the chromophore of pholasin has long been unknown, we finally concluded that DCL was the organic substance of pholasin, based on these results that DCL was active for the luminescence of pholasin and the DCL-DTT adduct was isolated from the native pholasin.…”
Section: )mentioning
confidence: 75%
“…41) Isobe's LC-MS and MS/MS analysis combined with counting the exchangeable protons was a powerful technique to identify the trace amounts of natural products using deuterium oxide as an eluent. [42][43][44][45][46][47] Although the structure of the chromophore of pholasin has long been unknown, we finally concluded that DCL was the organic substance of pholasin, based on these results that DCL was active for the luminescence of pholasin and the DCL-DTT adduct was isolated from the native pholasin.…”
Section: )mentioning
confidence: 75%
“…Ethyl 3-azido-4,6-difluorobenzoate (1) was prepared according to our previously reported method. 34 NMR spectra were recorded at −30, −20, or −10 °C on a spectrometer equipped with an HFX probe ( 1 H at 500 MHz, 13 C at 101 MHz, 19 F at 470 MHz, and 15 N at 51 MHz) or at −20 °C on a spectrometer equipped with an TXO cryoprobe ( 13 C at 201 MHz). Chemical shifts (δ) are reported in parts per million and referenced indirectly to tetramethylsilane (TMS) via the solvent residual signal.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Recently, we reported the formation of hemiaminals upon photolysis of aryl azides in 2,2,2-trifluoroethanol (TFE) at room temperature (rt). 34 Their structure and that of further photoproducts were established by extensive MS analyses, supported by comparison to the data of reference materials. 34,35 One of the photoproducts of 1 (Scheme 1) was found to be surprisingly stable in TFE at rt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 The primary amine was needed for the formation of the corresponding aryl azide which was used for photochemistry studies. 24 The formation of secondary ethyl amine 4 was possible due to small quantities of acetaldehyde formed via oxidative addition of palladium to the alcohol followed by βhydride elimination. 25,26 The equilibrium for this formation was far towards ethanol, however, due to the presence of the primary amine functioning as a trapping agent for the aldehyde a relatively large yield (41%) of the secondary amine could be isolated after 48 hours.…”
mentioning
confidence: 99%